The Effectiveness of TikTok as Strawdies Garden Promotion with the AISAS (Attention, Interest, Search, Action, Share) Model - Amalia, Infitakhu; Ferichani, Minar; Sundari, Mei Tri (HABITAT, 2025)
The internet has become an inseparable part of human life in today's era of technological development. Many of the current business players have utilized of this opportunity to promote their products online, especially through social media. This study aims to determine the effectiveness of promotion by looking at the impact of promotion on TikTok social media by AISAS model (attention, interest, search, action, share) and seeing the relationship between variables in it. The basic method of this study is quantitive descriptive method. The location determination method was purposive. The sample determination was carried out by purposive sampling with a total sample size of 120 respondents. A questionnaire was used to obtain the data. Data analysis using the Structural Equation Model (SEM) method with the Partial Least Square (PLS) approach. The results of the study show that promotion on TikTok social media had a significant impact on attention, interest, search, action, and share. Attention has a significant impact on interest. Interest has a significant impact on search. Search has a significant impact on action. Action has a significant impact on share. TikTok is considered effective in promoting Strawdies Garden because it has a significant impact on all dimensions of the AISAS model. This can be used as a reference for Strawdies Garden to continue to utilize TikTok as a promotional platform to attract consumers.